Proposed corporate citizenship program for standard hotels in Cavite. - Ramillo, Mark Roldan C. (2013)
Purpose of the Study This study attempted to impart knowledge, to introduce the concept of Corporate Citizenship in Standard hotels in Cavite, and most importantly, to set a program to improve the corporate citizenship efforts of the said hotels. Methodology The researchers identified the study as quantitative research. Quantitative research method is a scientific research design which involves observing and describing the behavior of the subject. The descriptive method of research was also employed in this study to simply describe data and characteristics about the population or phenomenon being studied. Since the researchers were measuring the level of performance of standard hotels to the key areas of corporate citizenship, the descriptive method of research was deemed most applicable. The sampling technique used in the study was Purposive or Judgmental Sampling and Neuman’s Method was used to identify the sample size. The study involved data gathering through survey questionnaires based on the Good Corporate Citizenship Assessment Model Test formulated by NHS and Sustainable Development Commission (2006). Survey method is a technique in data collection in which information of the randomly selected respondents is gathered through oral or written questioning. Statistical method such as weighted mean, ranking method, Frequency Distribution Table, T-test, chi-squared test and Friedman test were used. Summary of Findings This study aims to determine the level of performance of the management of Standard Hotels in Cavite Province with the areas of corporate citizenship. Specifically, the researchers have sought answers to the following questions: 1. What is the demographic profile of the respondents in terms of: 1.1. Age, 1.2. Gender, 1.3. Position? 2. How do the respondents observe the level of performance of the management of Standard Hotels in Cavite province based on key areas of the Good Corporate Citizenship model in terms of: 2.1. Travel, 2.2. Procurement, 2.3. Facilities management, 2.4. Workforce, 2.5. Community engagement, 2.6. Buildings? 3. Which among the key areas of Good Corporate Citizenship Model do hotels perform the most? 4. How do the evaluation of respondents on corporate citizenship practices of the said hotels compare? 5. How are the profile variables of the respondents and their observation on corporate citizenship practices of standard hotels in Cavite related? 6. Based on the results of the survey, what corporate citizenship program can be proposed? Based on the analysis of data, the researchers arrived at the following findings: 1. Socio – demographic profile of Respondents 1.1. As to the age distribution of the respondents, it revealed that 58.9 percent of the total number of respondents was at the 18-27 age group, while 21.4 percent are in the 28-37 age group. Moreover, the 38-47 age group got 17.0 percent and the 48-60 age group got the lowest percentage with 2.7 percent, respectively. The results denote that most of the employees of the standard hotels are at the young adult age group. 1.2. As to gender distribution of respondents, there is an equal distribution of respondents in both genders, which got 50 percent each. This indicates that male and female employees of the hotels have given an equal chance and opportunity to answer the questions on corporate citizenship of their respective hotels. 1.3. As to the distribution of respondents in terms of position, the survey shows that out of 112 respondents, 92 respondents are rank and file employees and 20 are managers and supervisors. Since the study has used Purposive or Judgmental Sampling, the distribution of participants in terms of position has been set upon by the researchers and therefore yielded the said results. 2. Level of Performance to Key Areas of Good Corporate Citizenship Model 2.1. In terms of Travel, the indicator on providing facilities that help encourage employees, guests and visitors to consider green travel as the indicator which got the highest weighted mean with 5.85. The indicator which got the lowest weighted mean is encouraging employees to use alternative forms of travel like biking to work and car pooling with 4.54. The general weighted mean is 5.27, which can be interpreted as Getting There. It indicates that employees are considering green travel to be one of the efficient solutions to minimize the use of carbon emitting vehicles. 2.2. In terms of Procurement, the indicator on conforming with the ethical standards when dealing with suppliers got the highest weighted mean with 6.37 and assessing the products that are being delivered by the suppliers which should conform with the company’s policy obtained the lowest weighted mean at 6.12. The general weighted mean is 6.23 which can be interpreted as Getting There. The result signifies that the standard hotels are really thorough when it comes with choosing their prospective suppliers and dealers. 2.3. In terms of Facilities Management, the indicator which got the highest weighted mean is monitoring water use and consumption with 6.44. The indicator on following waste segregation scheme or program got the lowest weighted mean which got 6.14. The general weighted mean is 6.28 which can be interpreted as Getting There. This denotes that the hotels are really conscious about their water and energy consumption, rather than waste management. 2.4. In terms of Workforce, providing ways to protect its workforce and ensure that the workplace is safe, secure and free from bullying and harassment which got the highest weighted mean with 6.19; The indicator on employing local, disadvantaged, marginalized and long-term unemployed people within the community got the lowest weighted mean with 5.24. The general weighted mean is 5.81 which is interpreted as Getting There. It dictates that the safety and security of employees is the primary concern of the standard hotels. 2.5. In terms of Community Engagement, communicating with staff, visitors/guests suppliers and the local community with regards to their business plans with economic, environmental and social impacts, as the indicator that got the highest weighted mean among the six variables with 6.19. On the other hand, the indicator on including the participation of the community in making their business decisions got the lowest weighted mean with 5.47. The general weighted mean is 5.90, which can be interpreted as Getting There. This denotes that the standard hotels has an effective communication and are transparent with its staff, guests and more importantly with the local community with its business plans or decisions. 2.6. In terms of Buildings, the indicator which got the highest weighted mean is the location, orientation, energy supply, transport services and infrastructure development in planning the construction and or renovation of buildings with 6.32. The indicator which got the lowest weighted mean is monitoring the social, environmental and economic impacts of the building from planning, through completion and operation, with 5.69. The general weighted mean is 6.03 which is interpreted as Getting There. The results indicate that the standard hotels are considering the location, orientation, energy supply, transport services and infrastructure development in planning the construction and or renovation of their building plans. 3. Which among the key areas of Good Corporate Citizenship Model do hotels perform the most? Using Friedman Test, it was proven that there is a significant difference on the level of performance of the management of standard hotels in six key areas. Therefore, the null hypothesis is rejected. Median (IQR) perceived performance levels for travel with 5.40, procurement with 6.60, facilities management with 6.60, workforce with 5.93, community engagement with 6.00 and buildings with 6.17. Facilities Management obtained the highest mean value of 6.28 with verbal interpretation of ―Getting There‖. However, it is not significantly different with the mean value of 6.23 obtained by Procurement and Buildings with mean value of 6.03. These suggest that the hotel perform the most to Facilities Management, Procurement and Buildings . 4. How do the evaluation of respondents on corporate citizenship practices of the said hotels compare? Using Test of Difference (T-test) to measure if there is a significant diference between the evaluation of respondents (managers/supervisors and rank and file) on corporate citizenship, Travel got a computed t-statistic of 4.90 with its associated p-value less than 0.01 (t = 4.90, p < 0.01), Procurement got a computed t-statistic of 4.457 with its associated p-value less than 0.01 (t = 4.457, p < 0.01), Facilities Management with a computed t-statistic of 7.430 with its associated pvalue less than 0.01 (t = 7.430, p < 0.01), Workforce with a computed t-statistic of 4.973 with its associated p-value less than 0.01 (t = 4.973, p < 0.01), Community Engagement with a computed t-statistic of 7.788 with its associated p-value less than 0.01 (t = 7.788, p < 0.01) and Buildings with a computed t-statistic was 5.20 with its associated p-value less than 0.01 (t = 5.20, p < 0.01). Over all, the computed t-statistic was 5.571 with its associated p-value less than 0.01 (t = 5.571, p < 0.01). This implies that there is a highly significant difference on the over-all ratings given by the two groups of evaluators. It suggests that the managers and supervisors gave greater over-all ratings compared to the rank and file employees. It also signifies that the null hypothesis is rejected. 5. How are the profile variables of the respondents and their observation on corporate citizenship practices of standard hotels in Cavite related? Using chi squared test to measure if there is a significant relationship between the profile variables and their observation on corporate citizenship practices of standard hotels in Cavite, the results shows that in terms of AGE, Travel got a computed chi-square statistic of 1.835 with its associated p-value equals 0.399, Procurement with a computed chi-square statistic of 4.513 with its associated p-value equals 0.105, Facilities Management with a computed chi-square statistic was 1.779 with its associated p-value equals 0.411, Workforce with a computed chi-square statistic was 9.786 with its associated p-value equals 0.007, Community Engagement with a computed chi-square statistic was 7.125 with its associated p-value equals 0.028 and Buildings with a computed chisquare statistic was 2.243 with its associated p-value equals 0.326. This indicates that there is a significant relationship between key areas of Workforce and Community Engagement to AGE, while there is no significant relationship on the key areas of Travel, Procurement, Facilities Management and Buildings to AGE. Over all, the computed chi-square statistic was 2.897 with its associated p-value equals 0.235. This indicates that there is no significant relationship between AGE and the corporate citizenship practices of the hotels. The observations of the respondents to the over-all level of performance of the management are not related to their age. Therefore, in terms of age, the null hypothesis is accepted. In terms of Gender, Travel got a computed chi-square statistic was 2.948 with its associated p-value equals 0.229, Procurement with a computed chi-square statistic was 1.885 with its associated p-value equals 0.390, Facilities Management with a computed chi-square statistic of 2.897 with its associated pvalue equals 0.235, Workforce with a computed chi-square statistic of 5.019 with its associated p-value equals 0.081, Community Engagement with a computed chi-square statistic of 12.710 with its associated p-value equals 0.002 and Buildings with a computed chi-square statistic was 1.848 with its associated p-value equals 0.397. This indicates that Community Engagement has significant relationship to GENDER while Travel, Procurement, Facilities Management, Workforce and Buildings has no significant relationship to GENDER. Over all, the computed chi-square statistic was 12.710 with its associated p-value equals 0.002. This indicates that there is a highly significant relationship between the gender and the corporate citizenship practices of the hotels. The observations of the respondents to the over-all level of performance of the management are related to their gender. The male respondents tend to give greater over-all ratings compared to female respondents. Therefore, in terms of gender, the null hypothesis is rejected. Conclusions Based on the findings, the following conclusions were drawn: 1. The respondents were mostly 18-27 years old, with equal gender distribution and mostly are rank and file employees of the standard hotels. 2. Based on the results, the general weighted mean of all key areas (Travel, Procurement, Facilities Management, Workforce, Community Engagement and Buildings) can be interpreted as Getting There. 3. The key areas of Good Corporate Citizenship Model on which the hotels perform the most are: Facilities Management, Procurement, and Buildings. In addition, there is a statistically highly-significant difference in the level of performance of the management standard hotels among the six key areas, therefore, the null hypothesis is rejected. 4. There is a highly significant difference between the evaluation of respondents (managers/supervisors and rank and file employees) and their evaluation on the corporate citizenship practices of the said hotels (Travel, Procurement, Facilities Management, Workforce, Community Engagement and Buildings). Therefore, the null hypothesis is rejected. 5. There is no significant relationship between age and the corporate citizenship practices of the hotels while there is a significant relationship between the gender and the corporate citizenship practices of the hotels. Therefore, in terms of age, the null hypothesis is accepted while in terms of gender, the null hypothesis is rejected. 6. The researchers output is the Proposed Corporate Citizenship Program for Standard Hotels in Cavite. This proposed corporate citizenship program is consist of 6 sub programs, namely: Green Mile Program (Sustainable Travel Program), Green Alliance (Sustainable Procurement Program), Cash for Trash (Sustainable Facilities Management Program), Fitness and Beyond (Sustainable Workforce Program), Community Participation and Action (COMPACT) (Sustainable Community Engagement Program) and Build It Green (Sustainable Buildings Program). This program envisions positioning the Standard Hotels in Cavite as the premier ―sustels‖ or sustainable hotels in the Philippines. Recommendations Based on the conclusions, the researchers arrived at the following recommendations: 1. It is recommended that the hotels should devise a sustainable travel program with focus on alternative forms of travel such as biking. 2. Another suggestion is to have a sustainable procurement program with focus on guidelines in assessing products being delivered by the suppliers. 3. The hotels should also formulate a sustainable facilities management program with focus on proper waste management. 4. In order to have a stronger and more productive workforce, a sustainable workforce program should be created with focus on local employment and healthy workforce. 5. Making community a part of the business, the hotels should make a sustainable community engagement program with focus on include the participation of the community in making their business decisions and making them as key partners. 6. A sustainable building program with focus on green and sustainable building architecture while monitoring the social, environmental and economic impacts of the building from planning, through completion and operation is recommended to make the physical aspects of the hotel more sustainable. 7. The future researchers should use this study and its program as a baseline for more comprehensive researches on corporate citizenship.